2000
DOI: 10.1093/ije/29.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in a rural district of southeastern Tanzania: an application of the sisterhood method

Abstract: The maternal mortality ratio (MMR) was 448 maternal deaths per 100,000 live births (95%CI : 363-534 deaths per 100,000 live births). Maternal causes accounted for 19% of total mortality in this age group. One in 39 women who survive until reproductive age will die before age 50 due to maternal causes. The main cause of death provided by hospital data was puerperal sepsis (35%) and postpartum haemorrhage (17%); this is compatible with the main causes reported for maternal death in settings with high levels of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
2
8
0
3
Order By: Relevance
“…It has been suggested that one third of all maternal deaths occur before delivery and so may well be missed (14), not only by the indirect methods but also possibly by the direct method since the rare event of a maternal death depends on linkage to registered births. Since abortion is illegal in Ethiopia, most probably MMRs by all three methods are underestimates in respect of abortion related deaths (15). The epidemiological situation of HIV in the area is unfortunately unknown, but the clinical impression is that the area is still outside the main HIV-epidemic in Ethiopia, and we do not consider that AIDS-related deaths have greatly influenced MMR estimates.…”
Section: Discussionmentioning
confidence: 86%
“…It has been suggested that one third of all maternal deaths occur before delivery and so may well be missed (14), not only by the indirect methods but also possibly by the direct method since the rare event of a maternal death depends on linkage to registered births. Since abortion is illegal in Ethiopia, most probably MMRs by all three methods are underestimates in respect of abortion related deaths (15). The epidemiological situation of HIV in the area is unfortunately unknown, but the clinical impression is that the area is still outside the main HIV-epidemic in Ethiopia, and we do not consider that AIDS-related deaths have greatly influenced MMR estimates.…”
Section: Discussionmentioning
confidence: 86%
“…More deaths occurring in this radius is attributed to the fact that more than half of the women lived within a 0–5 km range and sought admission for delivering in this hospital. In a rural district setting, Font, et al showed a lifetime risk between the age groups as relatively stable and declining with no higher risk of mortality with older age, although lower age group (15–19 years) values were higher than the rest(5) with a very wide confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…7 The sisterhood method is an indirect method of obtaining population-based estimates of MMRs by asking a sample of women 15−49 years old how many of their sisters reached the age of 15 and how many of them died while pregnant, during delivery, or up to six weeks after the end of pregnancy. 8 Anemia is the main maternal consequence of malaria among pregnant women in malarious areas. 9 Thus, the marked increase in the MMR due to anemia during the peak period of malaria transmission suggests that malaria is a significant factor in maternal deaths in The Gambia.…”
Section: Discussionmentioning
confidence: 99%